2016
DOI: 10.31018/jans.v8i4.1036
|View full text |Cite
|
Sign up to set email alerts
|

Biology and feeding potential of Coccinella septempunctata (Linn.) against Lipaphis erysimi (Kalt) at different temperature regimes

Abstract: Biology and feeding potential of Coccinella septempunctata (Linn.) were studied in laboratory on 3rd instar nymphs of mustard aphid (Lipaphis erysimi Kalt.) at two different temperature regimes. At 30± 20C, fecundity, oviposition period, hatchability of eggs, male and female longevity (232±70.46, 12.8±3.91, 82.87±6.66, 22.70 ± 2.21and 26.60 ± 4.45, respectively) were higher and incubation period, pre-oviposition period, total grub duration and pupal duration (2.6±0.51, 6.5±3.53, 8.7 ± 1.63 and 5.1 ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
(2 reference statements)
2
3
0
Order By: Relevance
“…Pareek et al (2014) observed similar results of 237.37± 88.37 aphids as average consumption by fourth instar grub of C. septempunctata when reared on coriander aphid, Hyadaphis corriandri. The total number of aphids consumed during larval period was found to be 424.4± 2.78 aphids which is in agreement with the findings of Varshney et al, (2016) who reported total number of aphids consumed during larval period was 424.4± 2.78 aphids at 27± 2 0 C and in contrary when same was recorded at 23± 2 0 C, which was recorded to be 272.64± 1.19 aphids (Table 2).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Pareek et al (2014) observed similar results of 237.37± 88.37 aphids as average consumption by fourth instar grub of C. septempunctata when reared on coriander aphid, Hyadaphis corriandri. The total number of aphids consumed during larval period was found to be 424.4± 2.78 aphids which is in agreement with the findings of Varshney et al, (2016) who reported total number of aphids consumed during larval period was 424.4± 2.78 aphids at 27± 2 0 C and in contrary when same was recorded at 23± 2 0 C, which was recorded to be 272.64± 1.19 aphids (Table 2).…”
Section: Resultssupporting
confidence: 89%
“…The pre-oviposition period of C. septempunctata on mustard aphid, L. erysimi under laboratory conditions was varied from 4 to 13 with an average 7.92± 2.45 days. Varshney et al, (2016) reported pre-oviposition period to be 6.5± 3.53 days. The present studies revealed that oviposition of C. septempunctata on mustard aphid, L. erysimi under laboratory conditions was 13 to 26 days with an average of 21.6± 3.39 days and also reported oviposition period of C. septempunctata on mustard aphid, L. erysimi to be 12.8± 3.91 days.…”
Section: Resultsmentioning
confidence: 98%
“…The maximum number of aphids consumed by an adult was found in the treatment T 3 (556.33±2.84) and minimum in the treatment T (493.33±15.28), 5 while consumption by an adult in the remaining treatments were 510.33±7.18, 544.50±10.33 and 546.00±10.15 at temperature 20±2ºC, 25±2ºC and 35±2ºC and relative humidity 65-70%. The result is in conformity with the findings ofVarshney et al (2016) th who reported 4 grub and total grub instar consumption was 238.82±1.11 and 424.4±2.78 at 27± 2°C, 65±5% relative humidity. While the result is in partial conformity similar findings asMishra and Kanwat (2017) who reported that adult consumption…”
supporting
confidence: 92%
“…Su Wang et al (2013) also reported that variables temperature significantly affects the biological parameters of C. sexmaculata. Varshney et al (2016) also stated that the mean fecundity, incubation and hatchability percentage was 232±70.46, 2.6±0.51 and 82.87±6.66, respectively at 30 ± 2°C.…”
Section: Methodsmentioning
confidence: 93%
“…Similarly, (Singh et al, 2011) reported that the grub of C. septempunctata consumed 549.11 aphids in its total developmental period. (Varshney, Rachana and Bisht, 2016) reported that C. septempunctata feeds 424.4±2.78 aphids during its entire larval period. (Mishra and Kanwat, 2017) observed that the grub of C. septempunctata required 610.25 aphids for completion of larval development.…”
Section: Discussionmentioning
confidence: 99%